The Lililwan Project: study protocol for a population-based active case ascertainment study of the prevalence of fetal alcohol spectrum disorders (FASD) in remote Australian Aboriginal communities. Issue 3 (3rd May 2012) - Fitzpatrick, James P; Elliott, Elizabeth J; Latimer, Jane; Carter, Maureen; Oscar, June; Ferreira, Manuela; Olson, Heather Carmichael; Lucas, Barbara; Doney, Robyn; Salter, Claire; Peadon, Elizabeth; Hawkes, Genevieve; et al.
Abstract : Introduction: Anecdotal reports suggest that high-risk drinking in pregnancy is common in some remote Australian communities. Alcohol is teratogenic and may cause a range of lifelong conditions termed 'fetal alcohol spectrum disorders' (FASD). Australia has few diagnostic services for FASD, and prevalence of these neurodevelopmental disorders remains unknown. In 2009, Aboriginal leaders in the remote Fitzroy Valley in North Western Australia identified FASD as a community priority and initiated the Lililwani Project in partnership with leading research organisations. This project will establish the prevalence of FASD and other health and developmental problems in school-aged children residing in the Fitzroy Valley, providing data to inform FASD prevention and management. Methods and analysis: This is a population-based active case ascertainment study of all children born in 2002 and 2003 and residing in the Fitzroy Valley. Participants will be identified from the Fitzroy Valley Population Project and Communicare databases. Parents/carers will be interviewed using a standardised diagnostic questionnaire modified for local language and cultural requirements to determine the demographics, antenatal exposures, birth outcomes, education and psychosocial status of each child. A comprehensive interdisciplinary health and neurodevelopmental assessment will be performed using tests and operational definitions adapted for the local context. Internationally recognised diagnostic criteria will be applied to determine FASD prevalence. Relationships between pregnancy exposures and early life trauma, neurodevelopmental, health and education outcomes will be evaluated using regression analysis. Results will be reported according to STROBE guidelines for observational studies. Ethics and dissemination: Ethics approval has been granted by the University of Sydney Human Research Ethics Committee, the Western Australian Aboriginal Health Information and Ethics Committee, the Western Australian Country Health Service Board Research Ethics Committee and the Kimberley Aboriginal Health Planning Forum Research Sub-committee. Results will be disseminated widely through peer-reviewed manuscripts, reports, conference presentations and the media.